A Planning Based Framework for Controlling Hybrid Systems - Löhr, Johannes; Eyerich, Patrick; Keller, Thomas; Nebel, Bernhard (Proceedings of the International Conference on Automated Planning and Scheduling, 2012)
The control of dynamic systems, which aims to minimize the deviation of state variables from reference values in a continuous state space, is a central domain of cybernetics and control theory. The objective of action planning is to find feasible state trajectories in a discrete state space from an initial state to a state satisfying the goal conditions, which in principle addresses the same issue on a more abstract level. We combine these approaches to switch between dynamic system characteristics on the fly, and to generate control input sequences that affect both discrete and continuous state variables. Our approach (called Domain Predictive Control) is applicable to hybrid systems with linear dynamics and discretizable inputs.